Genetic basis of phenotypic diversity in C. stenophylla: a stepping stone for climate-adapted coffee cultivar development - Lahai, Paul M.; Aikpokpodion, Peter O.; Bah, Alieu Mohamed; Lahai, Mohamed T.; Meinhardt, Lyndel W.; Lim, Seunghyun; Ahn, Ezekiel; Zhang, Dapeng; Park, Sunchung (Frontiers in Genetics, 2025)
Climate change poses significant challenges to global coffee production, particularly for Arabica coffee, which is constrained by a narrow temperature tolerance and a limited genetic pool. This study explores Coffea stenophylla, a species native to West Africa, as a potential alternative to Arabica due to its adaptability to higher temperatures and high-quality flavor profile. Using genome-wide association studies (GWAS), we investigated the genetic basis of phenotypic diversity within C. stenophylla accessions from Sierra Leone, focusing on traits related to growth habit, fruit and seed morphology, and plant structural characteristics. Our findings revealed significant SNP-trait associations that underscore the genetic diversity and potential of C. stenophylla for breeding programs. Additionally, we identified potential selective sweeps and conducted functional enrichment analysis, which highlighted genes involved in inflorescence development and flowering regulation, indicating adaptive evolution to local climates. These results suggest that C. stenophylla retains valuable genetic diversity that can be harnessed for developing improved cultivars better suited to the climatic challenges.